Impact of Farming Practices on Productivity of Paddy Cultivation in Minor and Major Irrigation Schemes of Mahagirilla Agrarian Services Division of Kurunegala District in Sri Lanka - Kumari, O.; Sirisena, N.; De Silva, C.S. (University of Jaffna, 2019)
Food supply for ever growing population has become one of the challenges in Sri Lanka. Considering the paddy production statistics over 10 years period of Maha and Yala seasons, though the districts of Anuradhapura, Polonnaruwa and Ampara maintained higher average yield than national average yield, Kurunegala district had less average yield than national average yield during this period. Therefore, this study investigated the problems at farmers’ level for low productivity of paddy and identified the extent of adaptation of modern technological practices to overcome prevailing problems in Mahagirilla Agrarian Services Division. Two hundred farmers engaged in paddy cultivation from 16 Grama Niladhari divisions were selected from major and minor irrigation schemes as of 100 in each using random sampling method including. Major scheme is irrigated under Deduru Oya irrigation Scheme. Minor scheme is irrigated by wewa/ surface storage systems. The study revealed that the yield is positively correlated with method of planting, method of fertilizer application, duration of land preparation and irrigation method. The majority (79%) of farmers are a risk avert cluster who hesitate to adapt new technological practices to overcome prevailing problems. It could be recommended to organize awareness campaigns, build the confidence of farmers through activity oriented and result oriented trials, create a competitive work environment throughout the paddy farming areas, promote paddy cultivation among young generation and consistently providing subsidiaries through the government and non government organizations to reduce the yield gap.
Keywords: Fertilizing technology; Water management; Yield gap